Depresión y su repercusión en la conducta de un adulto de 21 años del cantón Babahoyo - Burbano Acosta, Renato Didier (2022)
This case study was carried out with the objective of determining the impact of depression on the development of adaptive behavior in a 21 year old adult from Babahoyo, in order to improve his mental health. This was carried out with the use of clinical history, clinical observation, semi-structured interview, in conjunction with psychometric tests "Beck Depression Inventory", "Plutich Suicide Risk Scale", "Rosenberg Self-Esteem Scale" and in addition, the use of cognitive behavioral therapy techniques such as examining evidence, explaining how thoughts create feelings, the methodology used is qualitative as it was useful when examining how depression and behavior in the patient. Through the use of the Manual of the International Classification of Diseases ICD 10 a diagnosis was made based on its criteria F32.1 Depressive disorder in a moderate episode, therefore, it was proposed to develop a psychotherapeutic scheme in order to reduce the patient's symptomatology and obtain a cognitive change in the patient. It is worth mentioning that this was elaborated under the cognitive-behavioral approach, which has been scientifically proven to be effective in treating alterations in thought and behavior.